Pengaruh Literasi Keuangan, Lifestyle Hedonis dan Sikap Keuangan Pribadi Terhadap Perilaku Keuangan Mahasiswa - Sri Fitri Wahyuni; Radiman Radiman; Dini Kinanti (Owner : Riset dan Jurnal Akuntansi, 2023)
Financial behavior is a person's ability to manage planning, budgeting, checking, managing, controlling, finding and storing daily financial funds. One of the factors that influence financial behavior is knowledge about financial literacy. The author's purpose is to determine the effect of financial literacy, hedonic lifestyle and personal financial attitudes on financial behavior in students of the economics faculty of management study program class l2018. The numberl of samplesl in thisl study werel 84 students usingl the slovinl formula. Thel analysis technique inl this studyl uses multiplel linear lregression, multiple correlationl determination, t testl and F ltest. Thel results ofl this studyl indicate thatl financial literacyl (X1) hasl a positivel and significantl effect onl financial behavior (Y). Hedonic Lifestyle (X2) hasl no effectl on financial behavior (Y). Personal financial attitude (X3) hasl no effectl on financial behavior (Y). Financiall literacy, hedonic lifestyle and personal financial attitudes simultaneously have a significant effect on financial behavior (studentsll of the 2018 classl of managementl study programl at Universitas Muhammadiyahl Sumatera Utara).